Abdominal Ectopic Pregnancy. A Case Report - Tahiluma Santana Pedraza; Jorge Luis Estepa Pérez; Bárbara Rafael Truy (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
Abdominal ectopic pregnancy is a rare condition, with very few cases reported in literature. It consists in the implantation of pregnancy in some of the structures in the abdomen by what is considered a rare variety of ectopic pregnancy, and is generally associated with a high rate of maternal and fetal mortality; in these cases maternal mortality is seven times higher than in the tubal pregnancy and up to 90 times higher than in normal pregnancy. We report the case of a patient with a history of bronchial asthma, who attended the Emergency Department of the health center of Montalbán, in the municipality Libertador, in the capital district of the Bolivarian Republic of Venezuela because of abdominal pain with nausea and gastric fullness. The patient was treated through surgical process. Through exploratory laparotomy, abdominal ectopic pregnancy was detected. Partial right oophorectomy was performed as well as exeresis of the embryonary sac.